; Policy evaluation on the basis of the Farm Accountancy Data Network - Ulrich Koester; Jens-Peter Loy (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2016)
68 () 1306/2013 : « () » (Verordnung (EU) Nr. 1306/2013). , () (. Farm Accountancy Data Network (FADN) / . Informationsnetz Landwirtschaftlicher Buchführungen (INLB), , . . -, , . , . -, , , , « » ( ), . -, - . . , . , (European Court of Auditors, 2016). – – According to recital (68) of the preamble to regulation (EU) No. 1306 /2013, `Each measure under the CAP should be subject to monitoring and evaluation in order to improve its quality and to demonstrate its achievements.' This policy brief investigates whether the officially-declared data set for policy evaluation, the Farm Accountancy Data Network (FADN), can be used to assess the impact that direct payments of the Common Agricultural Policy (CAP) actually have on official policy objectives. It is our opinion that FADN data are inadequate to be used in policy evaluation due to the specifics of selection of the sample. First, there is a mismatch between farms that are included in the sample and farms that are entitled to receive direct payments. Second, and possibly even more importantly, the information collected, so-called farm income, does not represent farmers' actual income. Third, the data are neither consistent in time nor between Member States. This policy brief reports on selected data problems for selected EU countries. The analysis leads to the final conclusion that the present setup of FADN data is inadequate for the data to be used to evaluate EU farm income policy. This conclusion is completely in line with the European Court of Auditors' Report (European Court of Auditors, 2016).
urn:nbn:de:gbv:3:2-113083
Keywords: 330